What's New in NSAID Pharmacotherapy: Oral Agents to Injectables. (December 2013) - Atkinson, Timothy J.; Fudin, Jeffrey; Jahn, Heather Lynne; Kubotera, Natsuki; Rennick, Amanda Leigh; Rhorer, Mary
Abstract: Objective: Nonsteroidal anti‐inflammatory drugs (NSAIDs) represent a critically important class of medications useful in numerous musculoskeletal and inflammatory diseases. The focus of NSAID use has recently centered on gastrointestinal (GI) side effects and potential cardiovascular toxicity. Innovative new oral and intra‐articular pharmaceutically engineered dosage forms are examined. We review recently developed intravenous NSAIDs and their potential advantages over oral products in the perioperative setting. Design: Databases searched included PubMed, Google Scholar, Ovid, and Athens. We contacted key U.S. and Japanese manufactures who are developing new and innovative NSAID technologies for inclusion in this overview. Early attempts at mitigating GI toxicity with oral agents combined with gastroprotective additives are outlined. Results: Contemporary technologies coupled with uniquely advanced pharmaceutical manipulations to improve safety and efficacy are discussed including combined vasodilating agent naproxcinod as the prototypical cyclooxygenase‐inhibiting nitric oxide (NO) donor; hydrogen sulfide‐releasing compounds to protect GI mucosa; glycoscience technologies combining the intra‐articular hyaluronic acid SI‐613 combined with NSAIDs; and nano‐formulated SoluMatrix submicron technologies that include diclofenac, indomethacin, naproxen, and meloxicam. Conclusions: New NSAIDs under development are intended to address GI and cardiovascular pitfalls inherent to current therapy options across the entire NSAID drug class. NO or hydrogen sulfide donating drugs, new reliable injectables for perioperative and inpatient use, novel intra‐articular extended‐release NSAIDs combined with IAHA, and nano‐formulations of submicron NSAIDs featuring delivery of decreased doses without diminished efficacy promise to afford innovative technologies that likely will be the future of NSAID therapy.